2002
DOI: 10.1091/mbc.02-02-0023
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Patterns in Human Liver Cancers

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of death worldwide. Using cDNA microarrays to characterize patterns of gene expression in HCC, we found consistent differences between the expression patterns in HCC compared with those seen in nontumor liver tissues. The expression patterns in HCC were also readily distinguished from those associated with tumors metastatic to liver. The global gene expression patterns intrinsic to each tumor were sufficiently distinctive that multiple tumor nodules from the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
402
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 778 publications
(433 citation statements)
references
References 36 publications
29
402
1
1
Order By: Relevance
“…As expected, prediction models based on gene expression profiles successfully discriminate HCC from non-tumor livers with expected high accuracy (Kim et al, 2004;Neo et al, 2004;Nam et al, 2005). Many studies have identified differentially expressed gene sets in HCC that differ according to etiological factors (Okabe et al, 2001), mutations of tumor suppressor genes (Chen et al, 2002), rate of recurrence (Iizuka et al, 2003), intrahepatic metastasis (Ye et al, 2003) and different stages (Nam et al, 2005). The results from these studies demonstrate that genomic-scale gene expression profiles recapitulate the well-known morphological distinctions of the tissues and suggest that the differences in gene expression patterns might be biologically relevant.…”
Section: Gene Expression Profiling Of Hccsupporting
confidence: 53%
“…As expected, prediction models based on gene expression profiles successfully discriminate HCC from non-tumor livers with expected high accuracy (Kim et al, 2004;Neo et al, 2004;Nam et al, 2005). Many studies have identified differentially expressed gene sets in HCC that differ according to etiological factors (Okabe et al, 2001), mutations of tumor suppressor genes (Chen et al, 2002), rate of recurrence (Iizuka et al, 2003), intrahepatic metastasis (Ye et al, 2003) and different stages (Nam et al, 2005). The results from these studies demonstrate that genomic-scale gene expression profiles recapitulate the well-known morphological distinctions of the tissues and suggest that the differences in gene expression patterns might be biologically relevant.…”
Section: Gene Expression Profiling Of Hccsupporting
confidence: 53%
“…Molecular analyses have shown that the HCC pathogenesis is a multifactorial and multistep process reflecting alterations derived from epigenetic instability, chromosomal instability and deregulated transcription (Chen et al, 2002;El-Serag and Rudolph, 2007). HCC death has been ranked the third most common cancer death worldwide as a result of poor prognosis due to the disease's heterogeneous nature and the high rate of intrahepatic metastasis that occurs in the dense vasculature of the liver (Tang et al, 2004;Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale gene expression profiling provides a powerful approach to identify transcriptional networks associated with upregulated signaling pathways, and to discover previously unrecognized tumor subtypes with distinct molecular and/or clinical phenotypes or responses to therapy (Golub et al, 1999;Alizadeh et al, 2000;Perou et al, 2000;MacDonald et al, 2001;Sorlie et al, 2001;Chen et al, 2002;Pomeroy et al, 2002;Shipp et al, 2002), including GBM (Sallinen et al, 2000;Ljubimova et al, 2001;Rickman et al, 2001;Lal et al, 2002). Gene expression profiling can also be used to detect distinct molecular signatures associated with specific mutations (Hedenfalk et al, 2001).…”
Section: Introductionmentioning
confidence: 99%